2020
DOI: 10.1039/d0qo01121e
|View full text |Cite
|
Sign up to set email alerts
|

Total and formal syntheses of fostriecin

Abstract: Two formal syntheses and one total synthesis of fostriecin (1) have been achieved, as well as, the synthesis of its related congener dihydro-dephospho-fostriecin. All the routes use the Sharpless dihydroxylation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…There have been various reports on the total synthesis of fostriecin since its discovery. In order to contribute to the facile synthesis of this naturally occurring polyketide, Dong et al [ 70 ] in 2020 reported a facile synthetic route for its total synthesis. In their methodology, trienyne 104 was converted to compound 105 via several steps.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…There have been various reports on the total synthesis of fostriecin since its discovery. In order to contribute to the facile synthesis of this naturally occurring polyketide, Dong et al [ 70 ] in 2020 reported a facile synthetic route for its total synthesis. In their methodology, trienyne 104 was converted to compound 105 via several steps.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Unfortunately, this study was terminated before reaching the MTD due to instability in storage and unpredictable purity . Nowadays, although the synthesis problem of fostriecin has been solved, the storage stability of fostriecin is still a problem that urgently needs to be addressed. When combined with carboplatin in ovarian cancer therapy, fostriecin can increase chemosensitivity, DNA damage, and micronuclei formation . The underlying antitumor mechanism includes the regulation of the DDR pathway mediated by PP4 .…”
Section: Small-molecule Modulators Of Pppasesmentioning
confidence: 99%